2015
DOI: 10.1016/j.actbio.2014.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Ca-phosphate biological materials by scanning transmission X-ray microscopy (STXM) at the Ca L2,3-, P L2,3- and C K-edges

Abstract: Several naturally occurring biological materials, including bones and teeth, pathological calcifications, microbial mineral deposits formed in marine phosphogenesis areas, as well as bio-inspired cements used for bone and tooth repair are composed of Ca-phosphates. These materials are usually identified and characterized using bulk-scale analytical tools such as X-ray diffraction, Fourier transform infrared spectroscopy or nuclear magnetic resonance. However, there is a need for imaging techniques that provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
59
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 84 publications
16
59
1
Order By: Relevance
“…They showed peaks at 136.7, 137.7 and 139 eV as well as a wider peak at 146.8 eV, similarly to the measured reference polyphosphate compound ( Figure 3). These XANES spectra could be assigned to polyphosphates based on existing libraries of P-containing compounds [40][41][42]. When transferred to MS-2 medium, both strains lost their polyphosphate granules, and produced Ca-carbonates only ( STEM-EDXS microanalyses showed that polyphosphate granules generally contained about 53%-63% of phosphorus (atomic proportion of P over P + Ca + K + Mg), ~13% to ~29% of calcium, ~2% to ~18% of magnesium and ~7% to ~15% of potassium (Figures 1d and 2d, Tables A1 and A3).…”
Section: Chemical Composition Of Carbonate and Polyphosphate Inclusiomentioning
confidence: 99%
See 1 more Smart Citation
“…They showed peaks at 136.7, 137.7 and 139 eV as well as a wider peak at 146.8 eV, similarly to the measured reference polyphosphate compound ( Figure 3). These XANES spectra could be assigned to polyphosphates based on existing libraries of P-containing compounds [40][41][42]. When transferred to MS-2 medium, both strains lost their polyphosphate granules, and produced Ca-carbonates only ( STEM-EDXS microanalyses showed that polyphosphate granules generally contained about 53%-63% of phosphorus (atomic proportion of P over P + Ca + K + Mg), ~13% to ~29% of calcium, ~2% to ~18% of magnesium and ~7% to ~15% of potassium (Figures 1d and 2d, Tables A1 and A3).…”
Section: Chemical Composition Of Carbonate and Polyphosphate Inclusiomentioning
confidence: 99%
“…Alignment of images of stacks and extraction of XANES spectra were done using the aXis2000 Software [39]. Carbonate inclusions were discriminated based on their different spectral signature at the C K-edge and the Ca L 2,3 -edges following the approach detailed by Cosmidis et al [40].…”
Section: Scanning Transmission X-ray Microscopy Analysesmentioning
confidence: 99%
“…SEM-energy dispersive X-ray spectra (EDS) were used for the determination of the chemical composition. The dominant phase was identified as a non-apatitic calcium phosphate matrix with average Ca/P atomic ratio of 1 were also identified throughout the specimen. The latter inclusions are related to minerals introduced from the deposition environment.…”
Section: Resultsmentioning
confidence: 99%
“…More specifically, Ca L 2,3 -edge near edge X-ray absorption fine structure (NEXAFS) and X-ray photoelectron (XPS) spectroscopies are applied in combination with extended X-ray absorption fine structure (EXAFS) spectroscopy, X-ray fluorescence (XRF) mapping and more commonly used techniques such as optical microscopy (OM) and scanning electron microscopy (SEM) for the assessment of diagenesis of two different types of paleontological remains: a hyena coprolite and a giant tortoise costal plate. The Ca L 2,3 -edge NEXAFS and Ca 2p photoelectron spectra provide quantitative information concerning the bone apatite and Ca-rich secondary phases [1][2]. OM and SEM are used to assess the morphology and chemical composition of the coprolite matrix and inclusions, whereas XRF maps were recorded to acquire complementary information on the distribution of P, Ca, Mn and Fe in the specimens [3][4].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, high spectral resolution ELNES from collagen alone have not been reported in the literature. However XANES measurements, which probe analogous transitions using soft X-rays rather than fast electrons, are available for both collagen alone [30], as well as collagen within bone samples [31] (figure 6b,d). In the X-ray microscope, collagen exhibits a major peak at ~288 eV assigned to a 1s → π* C=O transition in carbonyl groups, along with a minor peak at 285 eV and the broad resonance at ~300 eV from the 1s →σ* transition in C-C bonds [30].…”
Section: The Organic Phasementioning
confidence: 99%